Uji Toksisitas Akut Ekstrak Rimpang Kunyit pada Mencit : Kajian Histopatologis Lambung, Hati dan Ginjal (ACUTE ORAL TOXICITY OF TURMERIC EXTRACT IN MICE : HISTOPATHOLOGICAL STUDIES OF STOMACH, LIVER AND KIDNEY) - Winarsih, Wiwin; Wientarsih, Ietje; Sulistyawati, Nova P.; Wahyudina, Istifharany (Jurnal Veteriner, 2013)
This experiment was carried out to determine the mouse lethal dose (MLD50 of ethanolic extract ofthe turmeric (Curcuma longa) rhizomes following single oral administration and to evaluate thetoxicopathologic effects of the extract in certain organs ie stomach, liver and kidney. Forty five male micewere divided into nine groups. Four groups were treated orally with ethyl acetate fraction, four groups weretreated orally with hexane fraction of ethanolic turmeric extract, and one group was used as control. Theethyl acetate fraction groups were administered orally with the ethyl acetate fraction at doses of 7.5, 1.5,30 and 60 g/kg body weight. The hexane fraction groups were administered orally with the hexane fractionwith the dosage of 7,5, 15, 30 and 60 g/kg body weight. The control group received normal saline. MLD50 ofethyl acetate fraction was 27,98 gram/kg body weight by per oral administration. Oral MLD50 of hexanefraction was 19,50 gram/kg body weight. Histopathological features of the ethyl acetate and hexanefractions groups showed increased amount of parietal cells in stomach and parenchymal degeneration andnecrosis in their liver and kidney.
Keywords: turmeric extract, acute toxicity, LD50, histopathology